Mite sensitization among Latina women in New York, where dust mite allergen levels are typically low - Chew, Ginger L. (2009)
In New York (NY), Latinos often have greater asthma morbidity than other ethnicities, and dust mite sensitization is common despite low allergen levels. We investigated mite allergen exposure and sensitization in atopic and/or asthmatic women, the majority being Puerto Rican. Women (n=274) recruited for a birth cohort study were visited postnatally. Dust from their homes was analyzed for mite allergens (Der f 1, Der p 1, and Blo t 5). Serum was analyzed for total and allergen-specific IgE. Thirty-seven percent were sensitized to D. pteronyssinus, 34% to D. farinae, and 21% to B. tropicalis. Only 5% of NY homes had levels of Der f 1 > 2 μg/g; none had Blo t 5 or Der p 1 above this level. Caribbean or Latin American birthplace (a proxy for childhood exposure) was not associated with mite sensitization. Sensitization to D. pteronyssinus and D. farinae was associated with a report of doctor-diagnosed asthma (Odds ratio (OR) = 3.27, p = 0.003; OR = 2.81, p = 0.010, respectively); sensitization to any mite was associated with asthma medication use in the past 12 months (OR=3.12, p=0.004). These associations held even after adjustment for cockroach, mouse, and cat sensitization.